Income Misperception and Populism - Thilo Nils Hendrik Albers; Felix Kersting; Fabian Kosse (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
We propose that false beliefs about the own current economic status are an important factor for explaining populist attitudes. Along with the subjects' receptiveness to right-wing populism, we elicit their perceived relative income positions in a representative survey of German households. We find that people with pessimistic beliefs about their income position are more attuned to populist statements. Key to understanding the misperception-populism relationship are strong gender differences in the mechanism: Misperception triggers income dissatisfaction for both men and women, but the former are much more likely to channel their discontent into affection for populist ideas.
Keywords: D63; D72; D91; P16; 330; perception; income; populism